Burst Spinal Cord Stimulation: Review of Preclinical Studies and Comments on Clinical Outcomes. Issue 5 (12th February 2018) - Chakravarthy, Krishnan; Kent, Alexander R.; Raza, Adil; Xing, Fang; Kinfe, Thomas M.
Abstract : Background: Burst spinal cord stimulation (SCS) technology uses a novel waveform that consists of closely packed high‐frequency electrical impulses followed by a quiescent period. Within the growing field of neuromodulation, burst stimulation is unique in that it mimics the natural burst firing of the nervous system, in particular the thalamo‐cingulate rhythmicity, resulting in modulation of the affective and attentional components of pain processing (e.g., medial thalamic pathways). Study Design: A review of preclinical and clinical studies regarding burst SCS for various chronic pain states. Methods: Available literature was reviewed on burst stimulation technology. Data sources included relevant literature identified through searches of PubMed, MEDLINE/OVID, SCOPUS, and manual searches of the bibliographies of known primary and review articles. Outcome Measures: The primary outcome measure was to understand the mechanisms of action with regards to burst stimulation and to review clinical data on the indications of burst SCS for various chronic pain states. Results: We present both mechanisms of action and review uses of burst stimulation for various pain states. Conclusions: Burst stimulation offers a novel pain reduction tool with the absence of uncomfortable paresthesia for failed back surgery syndrome, diabetic neuropathic pain, and anesthesia dolorosa. Preclinical models have emphasized that the potential mechanisms for burst therapy could be related to neural coding algorithms that mimic the natural nervous system firing patterns, resulting in effects on both the medial and lateral pain pathways. Other mechanisms include frequency dependent opioid release, modulation of the pain gate, and activation of electrical and chemical synapses.